Representações Sociais sobre Envelhecimento Ativo de Pessoas Idosas com e sem o diagnóstico de Hiv/Aids - Ferreira, Olívia Galvão Lucena (2015)
In recent years, there has been a significant growth of the elderly population as a result of technological advances in health care and changes in the socioeconomic conditions. This changing of the population’s demographic profile is an important factor to understanding the Acquired Immune Deficiency Syndrome (AIDS) in older people, as it continues to increase the number of infection notifications with Human Immunodeficiency Virus (HIV) in this age group. However, older people living with HIV tend to have the effect of immune suppression more rapidly than other age groups, because they add to clinical manifestations of AIDS, the signs and symptoms of other illnesses that may be linked to aging, and thus can compromise their autonomy, functional independence and aging representation. Thus, this study becomes relevant to the implementation of actions that improve and/or maintain the health of the elderly, during the process of aging and well-being, also contributing with health professionals in the design and implementation of therapeutic and preventive action plans, targeting the health of the elderly. This study aims to analyze and compare the social representations of active aging, elaborated by elderly people living with and without HIV/AIDS. It is an exploratory study, using the theoretical framework of the Theory of Social Representations. Participate in the study, 48 elderly people, aged between 60 and 96 years, divided into two groups: older people with and without a diagnosis of HIV / AIDS. Data were collected from the Test of Free Association of Words and semi structured interviews and processed with the help of Iramuteq and Trideux software. The data collected and analyzed were interpreted subsidized in the theoretical framework adopted and presented in figures, charts and themes. The results correlate with each other, allowing inferences about the social representations on active aging permeated by positive and negative dimensions. For the active elderly stimulus, they highlight the most positive meanings and to the AIDS elderly stimulus, has been found themselves’ senses tied with the condition of being with the diagnosis of AIDS disease. Active aging depends on a variety of determining factors involving individuals, families and society. Providing a successful aging to the elder HIV positive person is possible through the combination of various sectors and use of transdisciplinary strategies to the promotion of health, allowing it to remain autonomous, independent and participatory society.